2018
DOI: 10.14686/buefad.412614
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Effect of Peer-Led Team Learning Model on University Students’ Exam Achievement in General Chemistry

Abstract: The purpose of this study was to compare freshmen engineering students' exam achievement in general chemistry course using peer-led team learning model and traditional instruction and to investigate the effect of this model on different achieving level students. A total of 128 students who were instructed by the same professor participated in the study. Throughout the semester, Peer-Led Team Learning (PLTL) model was implemented in the experimental group while traditional instruction was used in the control gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 37 publications
(96 reference statements)
1
2
0
Order By: Relevance
“…Similar results emerged in the studies conducted by Hockings et al (2008), Lewis (2011), andYoung andLewis (2022). Eren-Şişman et al (2018) compared the PLTL model with traditional teaching for general chemistry course achievement at a university in Turkey and found positive results, especially for low and medium-level successful students. In their study on university-level physics, Zorlu and Zorlu (2020) concluded that the students in the experimental group, in which the PLTL model was applied, had a more positive view of "the model encouraging active learning" than the control group.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…Similar results emerged in the studies conducted by Hockings et al (2008), Lewis (2011), andYoung andLewis (2022). Eren-Şişman et al (2018) compared the PLTL model with traditional teaching for general chemistry course achievement at a university in Turkey and found positive results, especially for low and medium-level successful students. In their study on university-level physics, Zorlu and Zorlu (2020) concluded that the students in the experimental group, in which the PLTL model was applied, had a more positive view of "the model encouraging active learning" than the control group.…”
Section: Resultssupporting
confidence: 79%
“…Thus, in this model, there is a process in which peer leaders and students interact with each other by conducting activities such as debate, discussion, and problem-solving in peer student groups under the guidance of peer leaders (Gosser et al, 2010). As seen in many studies in the literature (Eren-Şişman et al, 2018, Lewis, 2011, Wells, 2012, peer studies in this model start after the theoretical lessons. The teaching methods and routine used by the teacher in the teaching process are preserved since peer leaders get involved after the theoretical part of the lesson.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation